2021
DOI: 10.1007/s11469-021-00615-x
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of the Spanish Version of Fear of COVID-19 Scale: its Association with Acute Stress and Coping

Abstract: The COVID-19 is a “unique” stressor, which can produce physical and psychological trauma. Coping styles can buffer this psychological impact. Consequently, this paper aims to psychometrically adapt the Fear of COVID-19 scale (FCV-19S) to Spanish and examines the relationships between FCV-19S, stress response, and coping strategies. The sample comprised a convenience sample of 1146 participants (12–83 years), 880 from Spain (76.8%), and 266 from Dominican Republic (23.2%). Overall, the findings support a one-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
3
10
1
1
Order By: Relevance
“…This is in congruence to previous studies done to test the tool's psychometric properties. [7,9,41,43,48,49,52,56,57,63,68] Conversely, the results are inconsistent to that of other studies where 2 factor models, emotional and physical response, were found to be better fit in the bifactorial structure than that of the unidimensional structure found in the current study. [6,37,47,51,55,62,63,69,70] It is also important to note that in other studies, FCV-19s was found to have 1 factor and 2 factor models.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in congruence to previous studies done to test the tool's psychometric properties. [7,9,41,43,48,49,52,56,57,63,68] Conversely, the results are inconsistent to that of other studies where 2 factor models, emotional and physical response, were found to be better fit in the bifactorial structure than that of the unidimensional structure found in the current study. [6,37,47,51,55,62,63,69,70] It is also important to note that in other studies, FCV-19s was found to have 1 factor and 2 factor models.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies also demonstrated invariance between genders (Piqueras et al, 2021; Sakib et al, 2020) and healthcare workers versus nonhealthcare workers (Huarcaya-Victoria et al, 2020). Further, two studies showed invariance between age groups (younger vs. older, with the specific age threshold varying across studies; Huarcaya-Victoria et al, 2020; Piqueras et al, 2021; Sakib et al, 2020). Taken together, although former studies have been concerned with FCV-19S’s equivalency across a limited number of cultures (and some groups), no study has examined the scale’s equivalency globally via a standardized procedure of data collection in culturally diversified context (i.e., most world regions).…”
Section: Measurement Invariancementioning
confidence: 88%
“…Lastly, a recent study (Lin et al, 2021) across 11 countries (i.e., Bangladesh, Brazil, Cuba, France, Iran, Italy, Japan, New Zealand, Pakistan, Taiwan, United Kingdom), primarily based on datasets from previous studies on the psychometric properties of the FCV-19S, showed that a one-factor solution of the FCV-19S indicated partial scalar invariance across countries and scalar invariance across gender and age groups (i.e., child, young to middle-aged adult, older people). Other studies also demonstrated invariance between genders (Piqueras et al, 2021;Sakib et al, 2020) and healthcare workers versus nonhealthcare workers (Huarcaya-Victoria et al, 2020). Further, two studies showed invariance between age groups (younger vs. older, with the specific age threshold varying across studies; Huarcaya-Victoria et al, 2020;Piqueras et al, 2021;Sakib et al, 2020).…”
Section: Measurement Invariancementioning
confidence: 93%
See 1 more Smart Citation
“…In 4 out of 7 samples an AVE < .50 was found in at least one factor. Convergent validity issues (AVE < .50) with Spanish versions occurred in at least three more studies (Martínez-Lorca et al, 2020;Piqueras et al, 2021;Soto-Briseño et al, 2021). Another study by Huarcaya-Victoria et al (2022) confirmed a two-factor structure but item 5 had mixed loadings.…”
Section: Introductionmentioning
confidence: 98%